A Multivocal Method Modeling Cross-Cultural Research in Multilingual Educational Settings Connected Through a Transborder Migratory Circuit - Jennifer F Reynolds (Foro de Educación, 2019)
This article showcases a visual-ethnographic film technique for generating data of use to linguistic anthropological and sociolinguistic studies of educational settings. It also is being used to foster an intercultural dialog between parents, teachers, administrators, and bilingual early childhood educators and specialists positioned in school districts that serve the same population of students at different ends of a transborder migratory circuit. Findings from prior studies using an earlier version of the video-cued multivocal method employed content analysis to reveal key battleground issues characterizing preschool education, namely language of instruction, academics in the curriculum, multiculturalism and parental involvement (Tobin, Arzubiaga & Adair, 2013). Those studies, however, did not connect sending and receiving school districts. Their analytic approach to coding, moreover offered only a limited use of Bakhtinian concepts. Therefore, the article seeks to investigate how the method can be fine-tuned to better foreground, for instance, how forms of «translanguaging» in schools are made manifest in formal and informal ways as well as the language ideological positioning that emerges in respondents’ answers as they make concrete observations when engaging richly contextualized audio-visual cues evident in the video shortcuts.